Pelatihan POC Kulit Nanas dan Aplikasi Trichoderma sp. pada Cabai di Kecamatan Bati-Bati - Barokati Tsaniyah; Indah Indriani; Muhammad Agha Putra AL Fajrin; Nida Noor Rahmy; Muhammad Difa Prayogi; Fajar Sidiq; Anita Robiah; Haili Sholeh; Ahmad Lutfi Rahman; Ahmad Mukhlisin; Muhammad Dien Akbar Putra Rasiobar; Latifatul Azkiya; Erpan Maulana; Jamaludin Haqi; Amelia .; Mustaqiim Sarwokartiko (CV. ITTC INDONESIA, 2026)
Chili (Capsicum annuum L.) is an important horticultural commodity in Bati-Bati District, Tanah Laut Regency, South Kalimantan Province; however, its productivity is often constrained by anthracnose disease caused by Colletotrichum sp., which reduces both yield and fruit quality. Farmers still predominantly rely on chemical fungicides to control this disease, despite the associated risks of hazardous residues and environmental pollution. In addition, agricultural waste such as pineapple peels has not been optimally utilized as a source of liquid organic fertilizer (LOF). This community service activity aimed to improve the knowledge and skills of the Women Farmers Group (KWT) in Bentok Darat Village through training on the production of liquid organic fertilizer derived from pineapple peels and the application of Trichoderma sp. as a biological control agent against anthracnose disease. The methods employed included counseling sessions, demonstrations of LOF preparation, practical application of Trichoderma sp., and monitoring and evaluation using questionnaires. Data were analyzed descriptively based on observations and questionnaire responses to assess participants’ levels of understanding and acceptance before and after the activity. The results indicated a significant increase in participants’ knowledge and acceptance. Prior to the activity, participants’ understanding of LOF and Trichoderma sp. was low, at 36% and 0%, respectively. Following the activity, 100% of respondents agreed with the implementation of the introduced technologies and expressed willingness to apply them independently. Overall, this activity was effective in enhancing the capacity of the Women Farmers Group and promoting the sustainable adoption of appropriate agricultural technologies.